Public health nurses' caring behaviour can increase homecare patients' satisfaction - Syaharuddin Syaharuddin; Yoga Tri Wijayanti; Mery Kana; Suprapto Suprapto; Kens Napolion (Jurnal Ilmiah Kesehatan Sandi Husada)
Background: Caring behavior plays a vital role in the nursing profession, especially in public health settings. In-home care services, where patients receive medical attention in the comfort of their homes, the quality of care and patient satisfaction depends heavily on the nurse's ability to exhibit caring behavior.